Effect of export promotion programs on export performance: evidence from manufacturing SMEs - Wang, Xiaoting; Chen, Aihua; Wang, Huafeng; Li, Shengxiao (Journal of Business Economics and Management, 2017)
The objective of this paper is to examine how a firm’s participation in government export promotion programs (epps) may lead to a better export performance. Based on dynamic capabilities perspective, a mediated moderation model of epps on export performance was proposed and tested in Chinese manufacturing smes. The results show marketing implementation capabilities mediate the effect of information-related programs on export performance, and the financial aid-related epps moderate the process. The results contribute to the studies relating epps and export performance, as the results confirm the instrumental role of epps in enhancing export performance and examine the interplay between different types of epps. This study provides a guideline for managers as to how they can benefit from government epps. The findings also imply that policy makers should develop epps with a specific emphasis rather than a general goal of export performance. This study develops new insights on how export ventures exploit epps to develop useful capabilities. Also, the study expands current thinking on exporting by recognizing that different types of epps affect exporting.